Great again : - Donald J. Trump. (Threshold Editions, 2015)
In this book (previously published as Crippled America), we’re going to look at the state of the world right now. It’s a terrible mess, and that’s putting it mildly. There has never been a more dangerous time. The politicians and special interests in Washington, DC are directly responsible for the mess we are in